Predictors of good functional outcome in post stroke patient attending hospital raja perempuan zainab ii after 6 months. - Ahmad, Afiza Hanun (2012)
Stroke is the second leading cause of death and adult disability globally. It is anticipated that by 2020, stroke will have moved from the 6th to 4th leading cause of lost disability adjusted life years. To determine the predictors of good functional outcome in post stroke patients attending Hospital Raja Perempuan Zainab II (HRPZ II) after 6 months post stroke. The study included all stroke patients who were admitted to HRPZ II from December 2009 to December 2010. Patients were interviewed to assess their socio-demographic data and medical history. Then, clinical examinations were done to assess the stroke severity using Scandinavian Stroke Scale (SSS) and functional status based on Modified Barthel Index (MBI). The clinical data and investigations results upon admission were gathered from the medical records. Patients were reassessed at six months post stroke on the Traditional Complementary Medicine usage, rehabilitation service, carer and also functional status (using MBI). The response rate was 92%. They were 52 men and 41 women with mean age of 63.7 (10.3) years. Sixty-one point three percent had hypertension and 30.1% had diabetic. On admission 34.4% had good functional status and at six months later, 84.9% had good functional status. SSS score (p<0.05) and age (p<0.05) significantly predict good functional outcome. The prevalence of good functional outcome after 6 months post stroke was higher compared to other studies. Higher SSS score and younger age at occurrence of stroke significantly predict good functional outcome.